47th AIAA/ASME/ASCE/AHS/ASC Structures, Structural Dynamics, and Materials Conference<BR&amp;gt; 14th AIAA/ASME/AHS Adap 2006
DOI: 10.2514/6.2006-2201
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Pressure Cycle Induced Microcrack Damage in Linerless Composite Tanks

Abstract: The public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Department of Defense, Washington Headqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Furthermore, development of CNTs themselves that mimic the strength of the weakest carbon fiber (or slightly less) for incorporation in the composite structure could be used so that, when the ultimate strength of the CNT was exceeded and the CNT broke, the resistance would be greatly and permanently changed indicating potential carbon fiber breakage and impending failure of the tank of structure. With future research underway to improve and develop ultralight, unlined composite tanks for aircraft, launch vehicles, and in space propulsion (Mallick et al 2005;Ryan et al 2006), the need for health monitoring for these tanks becomes critical.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, development of CNTs themselves that mimic the strength of the weakest carbon fiber (or slightly less) for incorporation in the composite structure could be used so that, when the ultimate strength of the CNT was exceeded and the CNT broke, the resistance would be greatly and permanently changed indicating potential carbon fiber breakage and impending failure of the tank of structure. With future research underway to improve and develop ultralight, unlined composite tanks for aircraft, launch vehicles, and in space propulsion (Mallick et al 2005;Ryan et al 2006), the need for health monitoring for these tanks becomes critical.…”
Section: Resultsmentioning
confidence: 99%
“…One of the major components of an RLV is the cryogenic tank for propellant storage. The development of new lightweight tanks has been researched for several years, with lightweight carbon fiber composites being the major focus (Ryan et al 2006;DeLay 2011). However, during development of composite cryogenic tanks, there have been two incidents involving dramatic tank failure during testing (Marshall Space Flight Center 2000;NASA 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This model related micro-crack density to the global constitutive response and the material micro-crack fracture toughness. 77 Kaushik Mallick et al established an analytical expression for the effective elastic modulus of nanoclay-reinforced polymer matrix, which could be used for the development of matrix of linerless CPV. 151,152 In the later study, the analytic model was proposed for predicting the critical pressure at which the micro-cracks were initiated in the hoop plies under biaxial load.…”
Section: Simulation Methods Of Damage and Failure Of Composite Shell ...mentioning
confidence: 99%
“…And the analytic formula of the crack growth rate and the micro-crack energy release rate was established. 77 Fabian Hübner et al studied the fatigue crack propagation at low temperature (−50°C). It was found that the crack growth rate was decreased drastically, when the epoxy resins was toughened and underwent low temperature stress.…”
Section: The Experiments Study Of the Damage And Failure Of Composite...mentioning
confidence: 99%